Optimal combination of solar, wind, micro-hydro and diesel systems based on actual seasonal load profiles for a resort island in the South China Sea - Basir Khan M.R.; Jidin R.; Pasupuleti J.; Shaaya S.A. (Elsevier Ltd, 2023)
Carbon dioxide; Cost benefit analysis; Costs; Diesel fuels; Emission control; Energy resources; Fuel economy; Fuels; Hybrid systems; Maintenance; Maps; Meteorology; Optimization; Renewable energy resources; Wind; HOMER; Micro hydros; Solar; South China sea; Tioman; Economic analysis; diesel; economic analysis; electricity generation; environmental risk; optimization; renewable resource; resource availability; seasonality; solar power; Malaysia; Pacific Ocean; Pahang; Seribuat Archipelago; South China Sea; Tioman; West Malaysia